Peru : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper assesses the performance of Peru's alternative fiscal rules in supporting medium-term fiscal policy objectives. Peru has shown steady fiscal surpluses and declining debt vulnerabilities. Subnational government constrains to borrow internationally have been relaxed, which could become a concern in the future. Current debt levels are already low, which may allow the authorities to move quicker toward a structural balance rule, or even propose a small structural deficit, without jeopardizing debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet